AMERICAN DREAM IN THE EYE OF ASIAN IMMIGRANTS: A GENETIC STRUCTURALISM ANALYSIS OF KEVIN KWAN’S RICH PEOPLE PROBLEMS - Galant Nanta Adhitya; Apriliana Hapsari (International Journal of Humanity Studies (IJHS), 2022)
East, South, and Southeast Asians are often treated inferiorly in the U.S. Aggregately, the COVID-19 pandemic has brought racial issues against them to the surface. Thus, literature on and/or about inferior minorities needs to be written by authors who belong to them. It is because literary works are not created in a vacuum. External factors have a hand in their creation. Kwan’s Rich People Problems serves as the closure for the Crazy Rich Asians trilogy. As a Singaporean-born author who immigrated to the U.S., he is exposed to the American Dream myth. This research then aims to discover how he internalizes it in the novel. Employing Goldmann’s Genetic Structuralism, it operates the structuralism approach through the Marxist lens. It utilizes Kwan’s social class to determine his worldview manifested in the structure of the novel. While the novel is the source of primary data, his biography collected from relevant sources becomes secondary data. His take on American Dream crystalizes in form of the characterization and plot of the novel. He appends the characters with backstories and improvements. They are embedded with determination, perseverance, hard work, loyalty, and reinvention, revamping their poor beginnings into rich entrepreneurs, experts, employees, and trophy spouses.